2008
DOI: 10.1016/j.electacta.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficients and electrical conductivities for calcium chloride aqueous solutions at 298.15K and 310.15K

Abstract: a b s t r a c tExperimental values for mutual diffusion coefficients (interdiffusion coefficients) for CaCl 2 aqueous solutions at 298.15 K and 310.15 K, not available in the literature, were experimentally determined between 0.005 mol dm −3 and 0.1 mol dm −3 . The measurements were performed by using a conductimetric openended capillary cell. Values at infinitesimal concentration, D 0 , were also obtained. These data were analysed using the Onsager-Fuoss and Gordon models. In addition, molar conductance data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The diffusion coefficient (D) for calcium chloride (CaCl 2 ) in aqueous solutions at 310.15 K has been reported to be (1.601±0.02)×10 −9 m 2 /s (Ribeiro et al 2008) which is of the same order of magnitude that was calculated theoretically in this study.…”
Section: Model Formulationsupporting
confidence: 66%
“…The diffusion coefficient (D) for calcium chloride (CaCl 2 ) in aqueous solutions at 310.15 K has been reported to be (1.601±0.02)×10 −9 m 2 /s (Ribeiro et al 2008) which is of the same order of magnitude that was calculated theoretically in this study.…”
Section: Model Formulationsupporting
confidence: 66%
“…Calcium chloride is an important component frequently found in geological formations and in aqueous solutions involved in industrial processes. For that reason, its aqueous solutions have been the focus of extensive thermodynamic [74][75][76][77][78][79][80] and structural studies by neutron scattering 73,[81][82][83][84][85] , X-ray diffraction (XRD) [86][87][88][89][90][91][92][93] , extended X-ray absorption fine structure (EXAFS) [93][94][95][96][97] , electric conductance [98][99] , and molecular simulation 90,[100][101][102][103][104][105][106] . On the one hand, early wide angle X-ray scattering (WAXS) experiments on concentrated CaCl 2 solutions by Yamaguchi et al 89 and their re-interpretation of previous data from Caminiti et al 88 suggested the presence of CIP configuration at and a…”
Section: B) Illustration Of the Methodology For Model Systems Involvimentioning
confidence: 99%
“…where z 1 and C 1 are the charge and the molar concentration of counterion in solution bulk, respectively; D is the diffusion coefficient of salt in solution; h is the intermembrane distance; T 1 and t 1 are the counterion transport number in membrane and in solution, respectively; V 0 is the linear solution pumping rate; and L is the length of desalination path. D value is taken to be equal to that at infinite dilution and 25 • C, which is 1.61 × 10 −9 m 2 /s for NaCl and 1.335 × 10 −9 m 2 /s for CaCl 2 [62]. For the experimental conditions, T 1 was assumed to be equal to 1 (as the membranes are highly selective for counterions in such dilute solutions, and at currents close to the limiting current density the input of water splitting was found to be negligible), t 1 was 0.603 for Na + in NaCl and 0.438 for Ca 2+ in CaCl 2 , h was 0.59 cm, and L was 2.15 cm.…”
Section: Current-voltage Curvesmentioning
confidence: 99%